Peripheral T-lymphocyte activation by human T-cell leukemia virus type I interferes with the CD2 but not with the CD3/TCR pathway. - Dodon, M D (1989)
Human T-cell leukemia virus type I (HTLV-I) is etiologically associated with adult T-cell leukemia, an aggressive lymphoproliferative disorder, and with chronic neurological diseases. In vitro it can infect several types of cells but transforms only human T lymphocytes. We have previously shown that HTLV-I viral particles, even when noninfectious, were able to activate human resting T lymphocytes, suggesting that this activation step may be important in the initiation of the lymphoproliferative process. In the present study, we first demonstrate that in contrast to other mitogenic stimuli, HTLV-I has the unique property to activate human resting T cells in the absence of accessory cells. We then investigate the relationship between HTLV-I-induced T-cell activation and the classical well-known pathways of activation, namely, the CD3/TCR and CD2 pathways. Competitive blocking experiments were performed in which the effects of monoclonal antibodies (MAb) to the CD3/TCR complex or to the CD2 molecule were evaluated on the HTLV-I activation of T cells and compared with that obtained on phytohemagglutinin (PHA)-stimulated cells. It was found that anti-CD3 or -TCR MAb strongly suppress the proliferative response of T cells to PHA, but are significantly less efficient in inhibiting the activation initiated by HTLV-I. By contrast, MAb recognizing specific epitopes of the CD2 molecule inhibit the proliferative response of T cells to PHA or to HTLV-I to the same extent. The results provide evidence that HTLV-I virions interfere mainly with activation via CD2 but not via the CD3/TCR complex. Considering the earlier expression of the CD2 molecule on human T-cell precursors, these observations might be relevant to the characterization of the differentiation stage at which viral infection could interfere with the development and the maturation of T lymphocytes.